Influence of mixed modifier fluoride on tuning the AC and dielectric properties of xBaF2–(50–x)CaF2–50B2O3 glass system - Sahapini, N. F. M.; Winie, Tan; Azlan, M. N.; Zaid, M. H. M.; Hisam, R. (Springer Heidelberg, 2023)
This study examined the effect of mixed alkaline earth modifier fluoride on AC conductivity and dielectric properties in xBaF2–(50–x)CaF2–50B2O3 (x = 5–35 mol) glass system. The impedance data showed a single-depressed semicircle with decreasing bulk resistance (Rb) with temperature. The change of σAC implied a non-linear relationship with BaF2, which induced a blocking effect on the mobility of the charge carriers at x ≤ 20 mol, indicating the Mixed Alkaline Earth Effect (MAEE). The abrupt increase at x = 25 mol was associated with the expansion of the glass network due to the formation of Non-Bridging Oxygen (NBO). All glass samples followed the Overlapping Large-Polaron Tunneling (OLPT) model for the conduction mechanism. The change in ε′ more prominent in low-frequency regions, signifying that polarization was contributed mainly by the space charge polarization. Electrical modulus analysis revealed non-Debye type relaxation, indicating temperature- and composition-dependent dynamic ion processes..